2005
DOI: 10.1002/anie.200462126
|View full text |Cite
|
Sign up to set email alerts
|

In‐Plane Bishomoaromaticity in Tetranitrogen Dianions: Solid‐State, Solution, and Electronic Structures

Abstract: Na4N8 cuboctahedra containing nearly planar N4 polygons make up, in the solid state as well as in solution, the core of the dimer structures of remarkably persistent bishomoaromatic dianions, which are generated by reduction of preoriented bisdiazenes by sodium. As to the nature of the transannular NN interactions (dN‐N= 2.5–2.8 Å) quantum chemical calculations disclose long bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
6
1
Order By: Relevance
“…Although rare, similar trans-annular O,S‚‚‚Sb interactions have been topologically characterized based on theoretical calculations in dibenzostibocines; 47 S‚‚‚N in 1,5-triazocine; 49 S‚‚‚S in S 8 2+ ; 50,51 Se‚‚‚Se in Se 8 2+ 50 and N‚‚‚N in tetranitrogen dianions. 52 The C‚‚‚C interactions in [2.2]paracyclophane 53 and Si‚‚‚N in 1-methylsilatrane 54 have been analyzed based on both experimental and theoretical data. The N‚‚‚N critical point properties reported here are slightly smaller than in ref 52, which correlates with the longer N-N distance.…”
Section: Resultsmentioning
confidence: 99%
“…Although rare, similar trans-annular O,S‚‚‚Sb interactions have been topologically characterized based on theoretical calculations in dibenzostibocines; 47 S‚‚‚N in 1,5-triazocine; 49 S‚‚‚S in S 8 2+ ; 50,51 Se‚‚‚Se in Se 8 2+ 50 and N‚‚‚N in tetranitrogen dianions. 52 The C‚‚‚C interactions in [2.2]paracyclophane 53 and Si‚‚‚N in 1-methylsilatrane 54 have been analyzed based on both experimental and theoretical data. The N‚‚‚N critical point properties reported here are slightly smaller than in ref 52, which correlates with the longer N-N distance.…”
Section: Resultsmentioning
confidence: 99%
“…For example, despite formal 6p electrons in the π-system of N 4 2– , the corresponding NICS(1) is close to zero. Conversely, σ-aromaticity is higher, which was also found in the case of in-plane bishomoaromaticity of specifically preoriented bisdiazenes forming cyclic tetranitrogen dianions . It is also interesting to estimate ring strain energies (RSE) of the N 4 x – rings.…”
Section: Results and Discussionmentioning
confidence: 83%
“…Conversely, σ-aromaticity is higher, which was also found in the case of in-plane bishomoaromaticity of specifically preoriented bisdiazenes forming cyclic tetranitrogen dianions. 59 It is also interesting to estimate ring strain energies (RSE) of the N 4…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of some compounds with planar cyclic normalN42 ions are reported earlier . Geier et al in a combine experimental and theoretical study revealed the in‐plane bis‐homoaromaticity in tetranitrogen dianions. Exner et al showed that two electron reduction of comparably proximate bis‐diazenes presents the doorway to the nonclassical cyclic delocalized normalN42 dianion.…”
Section: Introductionmentioning
confidence: 84%